(untitled) (Research, Society and Development, 2023)
Soybean (Glycine max (L.) Merril) is one of the most important crops in Brazil, being cultivated in most of the Brazilian territory. The objective of the study was to evaluate the ecophysiology of soybean plants in response to crop densities and sowing times. The experimental design used was randomized blocks in a factorial scheme with two sowing dates that is, november 15 and december 14, 2018) and with five plant densities (160, 200, 240, 280 and 320 thousand plants per hectare), with four repetitions. The evaluated characters were: chlorophyll “a” and “b”, leaf area index, root dry matter, stem dry matter, leaf dry matter, pod dry matter, number of pods per plant, height at R1 stage, number of reproductive nodes and yield per plant. Soybean cultivated in the second half of november favors higher levels of chlorophyll in leaves, greater accumulation of dry matter in roots, stems and leaves, as well as increased productivity. There were no significant correlations between leaf area index and plant height in stage R1, with the productivity index. Soybean cultivation at lower densities favors a greater number of reproductive nodes, number of pods and productivity per plant, expressing the phenotypic plasticity of the crop.